A geometrical point of view on linearized beta-deformations - Mikhailov, Andrei [UNESP]; Milian, Segundo P. [UNESP] (Springer, 2019)
It is known that the supermultiplet of beta-deformations of N = 4 supersymmetric Yang-Mills theory can be described in terms of the exterior product of two adjoint representations of the superconformal algebra. We present a supergeometrical interpretation of this fact, by evaluating the deforming operator on some special coherent states in the space of supersingletons. We also discuss generalization of this approach to other finite-dimensional deformations of the N = 4 supersymmetric Yang-Mills theory.
Keywords: Supergeometry; AdS; CFT correspondence; Representations of Lie superalgebras; Twistor theory; Scattering amplitudes